The Effect of Acidity Condition (pH) on The Color Change of Anthocyanin Compound from Butterfly Pea Flower Extract (Clitoria ternatea) - Saputri, Desi Riana; Listyadevi, Yuniar Luthfia; Adiwibowo, Muhammad Triyogo; Damayanti, Damayanti; Auriani, Wika Atro; Fahni, Yunita; Sanjaya, Andri; Yusupandi, Fauzi; Yuniarti, Reni; Zega, Fidel Abdiman; Ikhlas, Fikri Rahmatul (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2023)
An Indonesian plant called the butterfly pea flower (Clitoria ternatea) is being cultivated to take advantage of the antioxidant properties of its anthocyanin concentration. Several solvents must be used to acquire anthocyanins from butterfly pea flower extract during the extraction procedure. Flowers have many various anthocyanin compositions and exhibit a range of colors. These color differences are utilized in food and beverages as natural colorants. The purpose of this study is to ascertain how the anthocyanin chemicals in butterfly pea flowers respond to acidic conditions in terms of color stability. The extraction was placed over the course of 18 hours with an ethanol solvent at a 60% concentration, and it was evaporated using a rotary evaporator at a temperature of 60°C. Anthocyanin extract of Butterfly pea flower was examined to investigate how pH changes affected color. The anthocyanin extract that had been obtained was subjected to acidity tests at pH 1 to 14. Anthocyanins become more stable in an acidic or low pH environment, giving an object its red color. While this continues, greater anthocyanin pH values will cause blue color fading. When anthocyanins have a high or low pH, it significantly affects food coloring.